VD_FINDINFO HC / 2010 / 383 vom 1. April 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE, MINIMUM VITAL | 276 al. 1 CC, 276 al. 2 CC, 280 al. 2 CC, 285 CC, 451 ch. 2 CPC